High-performance polymer ionomer-ionic liquid membrane IPMC actuator - Lee, Jang-Woo; Hong, Soon Man; Koo, Chong Min (SPRINGER, 2014)
A high-performance ionic polymer-metal composite (IPMC) actuator based on a polyelectrolyte membrane has been constructed from a poly((t-butyl-styrene)- b-(ethylene-r-propylene)-b-(styrene-r-styrene sulfonate)-b-(ethylene-r-propylene)- b-(t-butyl-styrene)) (tBS-EP-SS-EP-tBS; SSPB) pentablock copolymer ionomer and the ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide (BMImTFSI). The SSPB copolymer ionomer had microphase-separated morphology comprising alternating styrene-rich ionic channel regions and aliphatic EP-rich non-ionic regions, on the several tens of nanometers scale (average diameter of ionic channel regions ca. 20 nm), whereas the most commonly used Nafion contained narrow ion clusters of less than 4 nm. The large ionic channels of SSPB enabled better transport of such bulky ions as IL ions, and endowed the SSPB-BMImTFSI membrane with ionic conductivity superior to that of the Nafion-BMImTFSI membrane (SSPB-BMImTFSI: 1.01 x 10(-4) S/cm, Nafion-BMImTFSI: 0.49 x 10(-4) S/cm). The SSPB-BMImTFSI membrane-based IPMC actuator generated a larger and faster electromechanical response than the Nafion-based IPMC.
Keywords: RADIATION-GRAFTED FLUOROPOLYMERS; METAL COMPOSITE ACTUATORS